Kerajinan souvenir dan asesoris rumah tangga dari limbah majalah bekas bagi santri Pondok Pesantren DDI Mangkoso - Pattaufi Pattaufi; Ramly Ramly; Bakhrani A. Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The purpose of the Community Partnership Program (PKM) This is a group of students from the Islamic BoardingSchool DDI Mangkoso Barru Regency (partners) having: (1) Increasing the knowledge and skills to use used magazine waste tobe used as souvenirs and household accessories that can be of artistic and economic value, (2 ) Improving skills in designingsouvenirs and household accessories from used magazine waste which has artistic and economic value, (3) Increasing skills ofrolling up used magazines to be used as souvenirs and household accessories that can be of artistic and economic value, (4)Increasing skills in making and assembling frames household souvenirs and accessories with recycling of work magazine wastecan be of artistic and economic value, (5) Improving the skills of finishing work souvenirs and household accessories of workmagazine waste can be of artistic and economic value, (6) Increasing knowledge about entrepreneurial souvenirs and homeaccessories ladder from waste m invitations to work can be of artistic and economic value. The target audience was the studentsgroup of Pondok Pesantren DDI Mangkoso Barru District (male and female students who were trained directly). The methodused in the delivery of material using the method of lectures, discussions and questions and answers, while the application ofstudents using demonstrations. The results achieved in the implementation of the Community Partnership Program (PKM). Thisis a group of students from the Boarding School DDI Mangkoso Barru District (partners) can: (1) Know and skillfully utilizeused magazine waste to be used as souvenirs and household accessories that can be of artistic and economic value, ( 2) Skillfuldesign of household souvenirs and accessories from used magazine waste that has artistic and economic value, (3) Skillful ofrolling old magazines to be used as souvenirs and household accessories that can be of artistic and economic value, (4) Skillful inmaking and assembling frames for souvenirs and household accessories with recycled used magazine waste that can be of artisticand economic value, (5) skilled finishing work of souvenirs and household accessories of used magazine waste that can be ofartistic and economic value, (6) Knowing about entrepreneurial souvenirs and household accessories from used magazine wastethat can be of artistic and economic value.